Delusion and Madness of the Crowds: Collective Perception in Pakistani Exchange Markets - Ullah, Furqan; Ullah, Hamid; Jan, Shahid; Asif, Muhammad; Mahreen, Faiza (The journal of contemporary issues in business and government, 2021)
The current study attempts to examine the associationbetween collective perception and exchange rates in Pakistan. We argue that people search online for information on currency exchange rates,and this online searching activity is transformed into data that could reflect people‟s interest in a given currency.The current study used Google Trends data of seven pairs of currencies to account for the level of interest in these currencies in Pakistan. Pairs of currencies include United Arab Emirates Dirham, Saudi Arabian Riyal, US dollar, Kuwaiti dinar, Qatari riyal, Omani riyal, and Canadian dollar against Pakistani rupees. Currencies are selected based on the highest level of remittances received in these currencies. The study has utilized data from 2010 to 2019 and used vector-autoregressive models forestimations.The results showed a significant impact of the collective perception measured through google trends data on exchange rates in Pakistani exchange markets.The authors analyzed the Google trends search queries for only seven pairs of currencies against the exchange rate in Pakistan. To be safe in the current and future, Investors in foreign and local currency exchange markets can benefit from the findings of this study at large. So, we argue that investors seeking information on exchange rate trends in Pakistan could utilize Google Trends information to forecast the future and make decisions accordingly. Google is widely used globally and hence in Pakistan due to the emerging trends of heavily relying on google searches for so many reasons. More specifically, exchange rates are searched on google, and thus google trends show the trends per click. This study is the first to investigate the google trends search data associated with the exchange rates in Pakistani markets with a broader view of collection perception in Pakistan.